IMPLEMENTATION OF MULTI COMMUNICATION DIRECTIONS IN ISLAMIC EDUCATION FOR IMPROVING LEARNING OUTCOMES - Hamlan Andi Baso Malla; Muhammad Atfal (Jurnal Dikdas, 2019)
Multidirectional is communication that do not only involve dynamic interaction between one learner and another. The teaching and learning process with this communication pattern leads to the teaching process that develops the optimal activities of learners, so that it fosters active learning learners. There are five strategies that can be developed in an effort to create / build effective communication, namely: respect, empathy, audible, clear meaning, humble. in the learning process at the classroom to use multi-directional communication in Islamic education subjects in SMP Negeri 2 Palu, there are several steps that must be passed by the teacher, including the following: 1) Explaining the material to be taught, 2) Making groups if needed, 3) Sharing material to facilitate students, 4) Discussion here is where multi-direction communication occurs, 5) Evaluation, by giving practice questions to measure student learning outcomes.